Class II Phosphoinositide 3-Kinases as Novel Drug Targets - Falasca, Marco; Hamilton, J.; Selvadurai, M.; Sundaram, K.; Adamska, A.; Thompson, P. (American Chemical Society, 2017)
Â© 2016 American Chemical Society. The phosphoinositide 3-kinases (PI3Ks) are a family of lipid kinases central to regulating a wide range of important intracellular processes. Despite the vast knowledge around class I PI3Ks, the class II PI3Ks have been neglected, seemingly only due to the chronology of their discovery. Here we focus on the cellular functions of the three class II PI3K isoforms, PI3KC2Î±, PI3KC2Î², and PI3KC2Î³, in different cell systems and underline the emerging importance of these enzymes in different physiological and pathological contexts. We provide an overview on the current development of class II PI3 kinase inhibitors and outline the potential use for such inhibitors. The field is in its infancy as compared to their class I counterparts. Nevertheless, recent advances in understanding the roles of class II PI3 kinases in different pathological contexts is leading to an increased interest in the development of specific inhibitors that can provide potential novel pharmacological tools.